Tolmerus calceatus (Meigen) confirmed as a valid species separate from Tolmerus atricapillus (Fallén) (Diptera: Asilidae) - van Den Broek, Reinoud; Smit, John T.; Bree, Elias De; Beentjes, Kevin (Zootaxa, 2018)
The status of Tolmerus atricapillus calceatus (Meigen) is discussed. Based on morphological, ecological as well as genetic information it is concluded that Tolmerus calceatus stat. rev. should be treated as a valid species separate from T. atricapillus (Fallén). Characters to separate both are provided as well as a key to all Tolmerus species of northwestern Europe.